AN INVESTIGATION OF ACADEMIC WRITING PROBLEMS LEVEL FACED BY UNDERGRADUATE STUDENTS AT AL IMAM AL MAHDI UNIVERSITY- SUDAN - Amin Ali Al Mubarak (English Review: Journal of English Education, 2017)
Academic writing skills mostly involve the linguistic competence development of the students which many English Second Language learners may identify it as a challenging task. The main objective of this study is to look into various challenges encountered by English Second language students in academic writing in ordinary graduation project in the context of universities. Specifically, this research focuses on identifying the problems faced by the Arts Colleges within the University of Al Imam Al Mahdi, Sudan. The researcher used the student’s project graduation to investigate the problems encountered by the students when they used their academic writing skills. To state the obstacles recognized by the examined students in academic writing skills, the researcher employed a descriptive method. The findings of this research revealed the most problematic area faced by the students. Finally, the results of this research may help the scholars to reflect on teaching practices and urge the goverment to help teachers’ attempts to enhance the academic writing skills of their students at the University of Al Imam Al Mahdi, Sudan. Keywords: academic writing, students, problems.